2022
DOI: 10.3847/1538-4357/ac9d92
|View full text |Cite
|
Sign up to set email alerts
|

Contracting and Expanding Binary Black Holes in 3D Low-mass AGN Disks: The Importance of Separation

Abstract: LIGO/Virgo has detected several binary black hole (BBH) merger events that may have originated in the accretion disks of active galactic nuclei (AGNs). These events require individual black hole masses that fall within the pair instability supernova mass gap, and therefore these black holes may have been grown from hierarchical mergers. AGN disks are a prime environment for hierarchical mergers and thus a potential location for the progenitors of BBH gravitational wave events. Understanding how a BBH embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 83 publications
2
31
0
Order By: Relevance
“…They also find that their binaries contract. However, in the two-dimensional shearing box simulations of , they find that the question of binary contraction versus expansion depends on the thermodynamics of the disk, and in the three-dimensional shearing box simulations of Dempsey et al (2022), they find that that the semimajor axis of the binary is also important. By using Equation…”
Section: Defining Properties Of the Accretion Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…They also find that their binaries contract. However, in the two-dimensional shearing box simulations of , they find that the question of binary contraction versus expansion depends on the thermodynamics of the disk, and in the three-dimensional shearing box simulations of Dempsey et al (2022), they find that that the semimajor axis of the binary is also important. By using Equation…”
Section: Defining Properties Of the Accretion Flowmentioning
confidence: 99%
“…These prescriptions are often motivated by more detailed hydrodynamic simulations of accreting binaries (e.g., Antoni et al 2019), with hydrodynamic studies of embedded BBHs being only recently studied. These studies include two-dimensional global simulations (Baruteau et al 2011;Li et al 2021), and local shearing box simulations in both two Li & Lai 2022) and three (Dempsey et al 2022) dimensions. These simulations have generally focused on cases where the Hill radius of the embedded binary is larger than the scale height of the AGN disk; though often the scale height can be comparable or larger than the BBH sphere of influence.…”
Section: Introductionmentioning
confidence: 99%
“…As binaries perturb the gas distribution around them through gravity, the gas can also affect the binary orbit (e.g., Baruteau et al 2011;Stone et al 2017). Recent high-resolution hydrodynamics simulations have carefully diagnosed the binary-disk interaction and have shown that the interaction can lead to the contraction of embedded binaries for a wide range of binary parameters, varieties of thermal properties of the AGN disks, and different accretion prescriptions (Li et al 2021;Dempsey et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been proposed for facilitating the mergers of BBHs in AGN disks. For example, the dynamical evolution of BBHs can be affected by the gravity from the highly perturbed gas around them (e.g., Baruteau et al 2011;Stone et al 2017); recent highresolution hydrodynamics simulations have shown that, for some AGN disk parameters, such BBH-disk interac-tion may indeed help the BBHs contract in orbit (and possibly merge) (Li et al 2021(Li et al , 2022bDempsey et al 2022;Li & Lai 2022. BBHs embedded in an AGN disk may also be hardened and driven to mergers by a series of scatterings with other single BHs (e.g., Stone et al 2017;Leigh et al 2018;Samsing et al 2022), especially when the mutual orbital inclinations between the BHs are small.…”
Section: Introductionmentioning
confidence: 99%
“…The local shearing sheet/box model (Goldreich & Lynden-Bell 1965;Narayan et al 1987;Hawley et al 1995;Latter & Papaloizou 2017) is a strong tool to study various physical properties of differentially rotating systems. To date, local shearing box simulations have been applied to a variety of astrophysical problems, such as magnetohydrodynamical (MHD) turbulence (e.g., Matsumoto & Tajima 1995;Stone et al 1996;Kawazura et al 2022) excited by magnetorotational instability (MRI ;Velikhov 1959;Chandrasekhar 1961;Balbus & Hawley 1991), dynamical and thermal properties of protoplanetary disks (e.g., Kunz & Lesur 2013;Mori et al 2017;Pucci et al 2021) and accretion disks around compact objects (e.g., Hirose et al 2009;Dempsey et al 2022), heating accretion disk coronae (Io & Suzuki 2014;Bambic et al 2023), driving disk winds and outflows (Suzuki & Inutsuka 2009;Suzuki et al 2010;Bai & Stone 2013;Lesur et al 2013;Fromang et al 2013), acceleration of nonthermal particles (Hoshino 2015;Kimura et al 2016;Bacchini et al 2022), and amplification of magnetic fields in compact objects (Masada et al 2012;Guilet et al 2022).…”
Section: Introductionmentioning
confidence: 99%